First observation and branching fraction measurement of the Λ 0 b → D − s p decay - Aaij, Roel; Bachmann, Sebastian; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Kubat, Jakub; Leverington, Blake; Marks, Jörg; et al. (Journal of high energy physics, 2023)
Abstract: The first observation of the Λ0b → D−s p decay is presented using proton-proton collision data collected by the LHCb experiment at a centre-of-mass energy of √s = 13 TeV, corresponding to a total integrated luminosity of 6 fb−1.
Im Titel sind "0" und "b" untereinander geschrieben: "0" hochgestellt, "b" tiefgestellt
Im Titel sind "-" und "s" untereinander geschrieben: "-" hochgestellt, "s" tiefgestellt
The LHCb Collaboration: R. Aaij, S. Bachmann, M. Borsato, R. Caspary, G. Frau, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, J. Kubat, B. Leverington, J. Marks, M.P. Morgenthaler, R. Skuza, D. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov [und 1044 weitere]
Gesehen am 12.01.2024